Online administrative document tracking system for the University of the Philippines in Mindanao - Clemente, Rachelle J. (2005)
The Administrative Online Document Trucking System for the University of the Philippines in Mindanao was developed to cut down on administrative data management problems of the university. This study was developed to suit the university?s process of administrative document processing as well as to eliminate the traditional and decentralized tracking system the university is currently using. This tracking system also allows other authorized staff to enter information of the documents to be tracked, view the document?s whereabouts and generate reports (for queries) about the documents. At the same time, it maintains confidentiality through the password ID?s required in every port of the system. Over time the online database can build up an audit trail of the handling and workflow history of each document file, effectively in a more efficient optimum workflow
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2005